SINGLE SUBJECT RESEARCH: PEMBELAJARAN PERBANDINGAN SENILAI DAN BERBALIK NILAI BERPENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK SISWA SLOW LEARNER - Manikmaya, Pratita; Prahmana, Rully Charitas Indra (Journal of Honai Math, 2021)
Slow Learner students often have difficulty understanding mathematics content, one of which is direct and inverse proportion. This study aims to improve the student's understanding of the direct and inverse proportion material using the Contextual Teaching and Learning (CTL) approach. The research subject in this study was a single subject, namely Slow Learner student who studied in seventh grade in one of the Junior High School in Bantul district, Yogyakarta Special Region. This study used the Single Subject Research method with an A-B design. Researchers collected the data in this study through audio documentation, photos, videos, and written documentation. The data were then analyzed using analysis in conditions and between conditions. The results showed that students had an average score of learning outcomes that was 32 before being given intervention and had an average score of 78 after being given an intervention to implement learning with the CTL approach. This result shows that using the CTL approach can improve the understanding of Slow Learner student in understanding the direct and inverse proportion and minimizing the learning difficulties of Slow Learning student during teaching and learning activities.